Interpersonal interaction in inclusive education for students with disabilities - Dariya А. Fateeva; Tatiana V. Klimova; Marina L. Skuratovskaya; Larisa М. Kobrina (Rossijskij psihologičeskij žurnal.)
Introduction. Students with disabilities have general and specific components of the system of relations in the socio-cultural environment of the institute of higher education, which reflect their interpersonal interaction. The study reveals the hierarchical structure of meaning and value aspects of disabled students’ willingness for tolerant interpersonal interaction in inclusive education. Methods. To analyze specific features of disabled students’ value guidelines in inclusive education the study employed the survey questionnaire methods, the techniques for analyzing the disabled students’ orientation in the system of social relations, and the authors’ inventories for studying willingness for tolerant interpersonal interaction. Results. This section presents the experiment for studying the axiological aspects of the disabled students’ willingness for tolerant interpersonal interaction in inclusive education. Discussion. The study revealed students’ ideas about tolerant interaction in the sociocultural environment of the institute of higher education, their determinants, age components of the system relations, and also components of the system of relations typical for students with disabilities. The results of the study showed the levels of the disabled students’ willingness for interpersonal interaction. The factors that determine this willingness were described. The findings are of direct practical relevance for psychological and pedagogical support of students with disabilities and their social, professional, and personal development in the inclusive educational environment of the institute of higher education.